Egbert Jamieson & Francis Adams, The Municipal Code of Chicago 391-92 (1881) - (:unkn) unknown (My University, 1881)
Article XLIII. Parks and Public Grounds, § 1690: Prohibited the carry of firearms or throwing of stones or other missiles within any public park. Prohibited cutting, breaking, or in any way injuring or defacing the trees, shrubs, plants, turf, or any buildings, fences, bridges, or other construction or property within any parks.
Keywords: CARRY - CERTAIN PUBLIC PLACES